An Experimental Analysis of Embankment on Stone Columns (Journal of Engineering, 2014)
When embankment is constructed on very soft soil, special construction methods are adopted. One of the techniques is a piled embankment. Piled (stone columns) embankments provide an economic and effective solution to the problem of constructing embankments over soft soils. This method can reduce settlements, construction time and cost. Stone columns provide an effective improvement method for soft soils under light structures such as rail or road embankments. The present work investigates the behavior of the embankment models resting on soft soil reinforced with stone columns. Model tests were performed with different spacing distances between stone columns and two lengths to diameter ratios of the stone columns, in addition to different embankment heights. A total number of 21 model tests were carried out on a soil with undrianed shear strength ≈ 10 kPa. The models consist of stone columns embankment at spacing to diameter ratio equal to 2.5, 3 and 4. Three embankment heights; 200 mm, 250 mm and 300 mm were conducted. Three earth pressure cells were used to measure directly the vertical effective stress on column at the top of the middle stone column under the center line of embankment and on the edge stone column for all models while the third cell was placed at the base of embankment between two columns to measure the vertical effective stress in reinforced soft soil directly. The embankment models constructed on soft clay treated with ordinary stone columns at spacing ratio equal 2.5 revealed maximum bearing improvement ratio equals (1.21, 1.44 and 1.7) for 200 mm, 250 mm and 300 embankment heights, respectively and maximum settlement improvement ratio equals (0.78, 0.67 and 0.56) for 200 mm, 250 mm and 300 embankment heights, respectively.